Association between perfluorooctanoic acid exposure and degranulation of mast cells in allergic inflammation. Issue 5 (29th September 2016) - Lee, Jun‐Kyoung; Lee, Soyoung; Baek, Moon‐Chang; Lee, Byung‐Heon; Lee, Hyun‐Shik; Kwon, Taeg Kyu; Park, Pil‐Hoon; Shin, Tae‐Yong; Khang, Dongwoo; Kim, Sang‐Hyun
Abstract: Perfluorooctanoic acid (PFOA) has wide applications, including as a raw material for converted paper and packaging products. With the widespread use of PFOA, concerns regarding its potential environmental and health impacts have increased. In spite of the known hepatotoxicity and genotoxicity of PFOA, correlation with PFOA and allergic inflammation is not well known. In this study, the effect of PFOA on the degranulation of mast cells and mast cell‐mediated allergic inflammation in the presence of FcεRI cross‐linking was evaluated. In immunoglobulin (Ig) E‐stimulated mast cells, PFOA increased the release of histamine and β‐hexosaminidase by the up‐regulation of intracellular calcium levels. PFOA enhanced gene expression of several pro‐inflammatory cytokines, including tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, IL‐6, and IL‐8 by the activation of nuclear factor (NF)‐κB in IgE‐stimulated mast cells. Also, PFOA exacerbated allergic symptoms via hypothermia, and an increase of serum histamine, TNF‐α, IgE and IgG1 in the ovalbumin‐induced systemic anaphylaxis. The present data indicate that PFOA aggravated FcɛRI‐mediated mast cell degranulation and allergic symptoms. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this study, the effect of PFOA on the degranulation of mast cells and mast cell‐mediated allergic inflammation in the presence of FcεRI cross‐linking was evaluated. In immunoglobulin (Ig) E‐stimulated mast cells, PFOA increased the release of histamine and β‐hexosaminidase by the up‐regulation of intracellular calcium levels. PFOA enhanced gene expression of several pro‐inflammatory cytokines, including tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, IL‐6, and IL‐8 by the activationof nuclear factor (NF)‐κB in IgE‐stimulated mast cells.